Practical optimism : the art, science, and practice of exceptional well-being - Varma, Sue (Avery, an imprint of Penguin Random House, 2024)
"As the first medical director and attending psychiatrist at the World Trade Center Mental Health Program, Dr. Sue Varma worked directly with civilian and first-responder survivors in the aftermath of 9/11. There, she met people at every point of the stress and trauma continuum. She saw devastation and stagnancy as much as she saw amazing resilience and growth. She asked herself: how do some people survive, even thrive, despite profound challenges? And how can we optimize the things we have control over, while buffering ourselves from stress? Through her work with patients and combining philosophy, her own personal experience, and a review of the latest research in psychology, psychiatry, medicine, and neuroscience, Dr. Varma discovered that the answer lies in cultivating an optimistic mindset that stays tethered to the real world and helps us make sound and reasonable decisions. This epiphany inspired Practical Optimism, Dr. Varma's powerful program with eight pillars to help all of us experience a sense of meaning, mastery, and self-acceptance and create lives filled with joy and purpose. Optimists, research has shown, are not just happier and more successful, but physically healthier. And if you're a natural-born pessimist? No problem: the most vital piece of the Practical Optimism program is that it is a practice, a skillset that we can choose to adopt and get better at every day. This book isn't about magical thinking. Practical optimists are resourceful, realistic, and thoughtful problem solvers who possess something of rare value: the inner resources to cope during a crisis and to use as fuel to flourish. Complete with self-assessment quizzes and exercises, Practical Optimism will help us all see the world for the better and reach our true potential. Practical Optimism is a scientific and tangible pathway to boosting health, happiness, resilience, success, and longevity"--